Cancer services and their initiatives to improve the care of indigenous Australians - Taylor, E.; Haigh, M.; Shahid, Shaouli; Garvey, G.; Cunningham, J.; Thompson, S. (Molecular Diversity Preservation International (MDPI), 2018)
Â© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Indigenous Australians continue to experience significantly poorer outcomes from cancer than non-Indigenous Australians. Despite the importance of culturally appropriate cancer services in improving outcomes, there is a lack of awareness of current programs and initiatives that are aimed at meeting the needs of Indigenous patients. Telephone interviews were used to identify and describe the Indigenous-specific programs and initiatives that are implemented in a subset of the services that participated in a larger national online survey of cancer treatment services. Fourteen services located across Australia participated in the interviews. Participants identified a number of factors that were seen as critical to delivering culturally appropriate treatment and support, including having a trained workforce with effective cross-cultural communication skills, providing best practice care, and improving the knowledge, attitudes, and understanding of cancer by Indigenous people. However, over a third of participants were not sure how their service compared with others, indicating that they were not aware of how other services are doing in this field. There are currently many Indigenous-specific programs and initiatives that are aimed at providing culturally appropriate treatment and supporting Indigenous people affected by cancer across Australia. However, details of these initiatives are not widely known and barriers to information sharing exist. Further research in this area is needed to evaluate programs and initiatives and showcase the effective approaches to Indigenous cancer care.